The life and death of zombies: Evidence from government subsidies to firms - Satu Nurmi; Juuso Vanhala; Matti E. E. Virén (Bank of Finland, 2020)
We analyze the demographics of zombie firms and durations of zombie spells as well as their determinants, including an application on public subsidies using firm level population panel data from Finland. Firm-level analysis of firm demographics reveals that zombie-firms, as commonly defined in the literature, are often not truly distressed firms but rather companies with temporarily low revenues relative to interest payments. More importantly, we find that roughly a third of these firms are in fact growing companies and two thirds recover from the zombie status to become healthy firms. We also show that the increase of zombie firms over the past 15 years has mainly been driven by cyclical factors, as opposed to a secular trend. In our policy application on government subsidies to firms, estimation results strongly suggest that subsidy-receiving firms are less likely to die, regardless of the type of subsidy. However, with regard to recovery there is heterogeneity in the effects depending on the type of firm and the type of subsidy received. Thus, we do not find a robust positive association of subsidies with zombie recovery.
URN:NBN:fi:bof-202005142140
Keywords: D22; D24; G33; H25; L16; L25; O25; 330; Zombies; Misallocation; Firm exit; Firm growth; Subsidies; Productivity